Herbal hepatotoxicity: Difficulties in the diagnosis and treatment of liver lesions by borage oil (Research, Society and Development, 2025)
Introduction: The use of herbal medicines has increased over the past 20 years as a complementary therapy for various diseases. However, the commercialization of these products is not preceded by a guarantee of safety. This article aims to report the use of borage oil or Borago officinalis (BO), beneficial for menopause-related symptoms, however, it may contain pyrrolizidine alkaloids (AP), a hepatotoxic toxin. Methodology: a study of the patient's electronic medical record was conducted. Case report: 53-year-old woman admitted to emergency room with jaundice, asthenia, hyporexia and pain in the right hypochondrium (HD) for 10 days after use of the herbal medicine Niolix® (BO), being initially diagnosed with acute hepatitis induced by BO. Liver biopsy revealed intense lymphocyte inflammatory infiltrate, in addition to plasma cells, neutrophils and macrophages, with aggression to the limiting plaque and hepatocytes. After the end of the corticosteroid treatment, there was a new increase in aminotransferases and the appearance of autoantibodies, leading to the hypothesis of autoimmune hepatitis triggered by BO. Immunosuppressive treatment was instituted, with significant improvement in the condition. Conclusion: this report exemplifies the diversity of liver lesions induced by herbs, as well as drugs, supplements, and medications, calling attention to the strict follow-up of cases, with possible changes in diagnosis and conduct during treatment.